2017
DOI: 10.1016/j.seizure.2017.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Emergency computed tomography in patients with first seizure

Abstract: In FS patients, clinical information can be used to guide imaging decisions in the ED. However, if emergency imaging is not performed, urgent outpatient imaging and pre-imaging follow up should be secured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Positive CTB findings ranged from 12% to 41% in other studies. (15,22) The higher yield in our study suggests the need to perform a CTB in all first-episode seizure patients with no obvious extracranial cause of the seizure.…”
Section: Discussionmentioning
confidence: 71%
“…Positive CTB findings ranged from 12% to 41% in other studies. (15,22) The higher yield in our study suggests the need to perform a CTB in all first-episode seizure patients with no obvious extracranial cause of the seizure.…”
Section: Discussionmentioning
confidence: 71%
“…In this regard, Kotisaaari et al in 2017 performed a CT scan on 416 of the 449 patients visiting the emergency unit, among which 49 (12%) had emergent imaging findings in the CT scan. 4 de la Sayette et al, in a study on 387 patients over 50 years of age with late-onset epilepsy, reported that most patients for whom CT scan was performed had either normal results or evidence of cerebral atrophy. 9 In another study on children hospitalized due to afebrile seizure in Tehran, Iran, 90% of the CT scans were reported as normal, which is in accordance with our study.…”
Section: Discussionmentioning
confidence: 99%
“…6 In the study by Kotisaari et al, headache (odds ratio=3.62), movement symptoms (odds ratio=3.23), history of malignancy (odds ratio=3.05), unstable mental status (odds ratio=2.27) are dependent on the pathologic findings in the CT scan. 4 Therefore, one could rely on the clinical symptoms before requesting a CT scan in patients with a first-onset seizure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence supports the use of emergency computed tomography (CT) in only a subgroup of adults who present with a first seizure, where there is history of head injury, fever, immunosuppression, malignancy, focal motor or sensory onset of seizure, or where patients present with a persistently reduced level of consciousness. 5,6 This has been adopted into the UK Guidelines in Emergency Medicine Network (GEMNet) protocol on the management of first seizure in the emergency department (ED). 7 For the remainder of first seizure patients, brain imaging, usually magnetic resonance imaging (MRI), can be requested at an outpatient neurology or first seizure clinic.…”
Section: Introductionmentioning
confidence: 99%